Lilin Aromaterapi Lavender Dapat Menurunkan Tingkat Dismenore Primer - Mokoginta, Feigi; Jama, Fatma; Padhila, Nur Ilah (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Dysmenorrhea is the cramping, pain and other discomfort associated with menstruation. The incidence of menstrual pain in the world is very high, it is said that because it is estimated that> 50% of women in all countries experience menstrual pain. In Indonesia, the incidence of dysmenorrhea is 64.25% consisting of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. This study aims to determine the effect of lavender aromatherapy candles on the level of primary dysmenorrhea in female students of SMA Negeri 1 Kotamobagu. This study used a pre-experimental research type, with one group pretest-posttest design. Determination of the sample in this study using non-probability sampling with total sampling technique, where the sample in this study were all female students who experienced primary dysmenorrhea in class XI IPA A and XI IPA B, totaling 24 people. The analysis used was univariate and bivariate, where the relationship test was performed using the Wilcoxon statistical test. The instrument used was the Numeric Rating Scale (NRS). Samples were given lavender aromatherapy candles for 60 minutes when they felt menstrual pain. The results of this study indicate the value of Ï = 0.000, where the value of Ï <Î±, then Ha is accepted. So, it can be concluded that there is an effect of aromatherapy candles on the level of primary dysmenorrhea in female students of SMA Negeri 1 Kotamobagu. The suggestion of this study is that pain management can be done by non-pharmacological methods such as relaxation techniques using lavender aromatherapy candles without having to take pharmacological drugs and this research can be used as a reference regarding the effect of lavender aromatherapy candles on primary dysmenorrhea.